KEBERADAAN PENCEMAR ORGANIK PERSISTEN (POPs) DI LINGKUNGAN - Dewi Ratnaningsih; Nety Widayati; Arum Prajanti; Heni Puspita; Yunesfy Sofyan (Pusat Standardisasi Instrumen Kualitas Lingkungan Hidup Laboratorium Lingkungan (P3KLL), 2007)
Persistent Organic Pollutants (POPs) are organic compounds that have been banned or prohibited for all purposes. Prohibiting of those compounds did not guarantee that those chemicals will not found in the environment. It’s related to the persistency properties of POPs. In order to investigate the exixstent of POPs in the environment, PUSARPEDAL_KLH and The United Nation University (UNU) Japan has been cooperated to carry out environmental monitoring on POPs. River located in urban are with dense population has been selected as target location. Samples were collected for river water, river sediment and river bank soil. Besides river in urban area, agrigultural area and location has tendency used to be aplicated with high frequency of POPs were also investigated. Related to the POPs management, Indonesia has signed Stockholm Convension. Environmental monitoring on POPs was a kind of effort to support POPs management. All of POP compounds (Endrin, Dieldrin, Aldrin, HCB, Heptachlor, Chlordane, Mirex, DDT and its derivates including pp-DDT, op-DDT, ppDDD, ppDDE) except for toxaphene, PCB, Dioksin and Furan were analyzed as target compounds by using GCMS QP 2010. Monitoring result indicated that river located in urban area has more variative of POPs compared with agricultural area, with concentration range of 0.002 – 3.24 ppb in river water; 0.24-165 ppb in river sediment ; and 0.34 – 154 ppb in river bank soil. In Agricultural area, only DDT and its derivated were detected with higher concentration than in urban area ( 3.91 ppb in water, 713 ppb in sedimen and 1282 ppb in soil) Concentration of POPs detected in water was lower than in sediment or soil sample because of its lipophililicity property. Possibility illegal using of POPs can not be ignored, therefore monitoring of POPs in the environment and surveillance to the illegal using of POPs is neccessary to be executed. Increasing public awareness by education and campaign need to be done in order to minimize negative impact of POPs to the human being.